Impact of low-energy virtual monoenergetic imaging in photon-counting CT for pre-TAVI pelvic arteries visualization: cardiac radiology - Alizadeh, Leona Soraja; Booz, Christian; Vogl, Thomas J.; Lanzafame, Ludovica R. M.; Martin, Simon S.; Yel, Ibrahim; Gruenewald, Leon D.; Koch, Vitali; D’Angelo, Tommaso; Mazziotti, Silvio; Smolka, Kerstin; Braunegger, Grit; et al. (La Radiologia medica, 2025)
This study aimed to assess the impact of photon-counting computed tomography (PCCT) virtual monoenergetic images (VMI) on quantitative and qualitative parameters in abdominal and pelvic vascular imaging for transcatheter aortic valve implantation (TAVI) planning.